Silica Gel-Supported Tungstosilicic Acid: An Efficient Catalyst for Synthesis of Diacetals - Jin, Tong-Shou; Ma, Guo-Dong; Xie, Hong; Li, Tong-Shuang (Asian Journal of Chemistry, 2010)
An efficient and convenient method for synthesis of diacetals from aldehydes and ketones with pentaerythritol in refluxing benzene or toluene using silica gel-supported tungstosilicic acid as catalyst is described. This method provides several advantages such as neutral condition, high yields and environment friendly.